2008
DOI: 10.1186/bcr2206
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oestrogens but not oestrogen deprivation promote cellular invasion in intercellular adhesion-deficient breast cancer cells

Abstract: Introduction Anti-oestrogens have been the mainstay of therapy in patients with oestrogen-receptor (ER) positive breast cancer and have provided significant improvements in survival. However, their benefits are limited by tumour recurrence in a significant proportion of initially drug-responsive breast cancer patients because of acquired anti-oestrogen resistance. Relapse on such therapies clinically presents as local and/or regional recurrences, frequently with distant metastases, and the prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
5
25
0
Order By: Relevance
“…Cellular adhesion molecule has been proven to play a key role in tumor invasion and metastasis (25). E-cadherin Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular adhesion molecule has been proven to play a key role in tumor invasion and metastasis (25). E-cadherin Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Borley et al (260) reported that the antiestrogens tamoxifen and fulvestrant can promote an invasive phenotype in E-cadherin deficient ER + breast cancer cells through activation of sRC. however, estrogen deprivation mimicking the action of aromatase inhibitors did not promote invasiveness in the same cells.…”
Section: Emt Cscs and Endocrine Resistancementioning
confidence: 99%
“…The extracellular matrix invasion assay was performed essentially as described [12]. Briefly, the 24-well BioCoat Matrigel invasion chambers with 8-μm pore size coated with Matrigel (0.4 μg/mL) (BD Biosciences) were rehydrated according to the manufacturer's instructions.…”
Section: In Vitro Cell Invasionmentioning
confidence: 99%